2023
DOI: 10.1007/s11064-023-03893-0
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Perineural Injection of BoNT/A on Neuropathic Pain Induced by Chronic Constriction Injury of Sciatic Nerve in Rats

Abstract: This study was designed to investigate the analgesic effect of perineural injection of BoNT/A on neuropathic pain induced by sciatic nerve chronic constriction injury (CCI) and possible mechanisms. SD rats were randomly divided into Sham group, CCI group and BoNT/A group. Paw mechanical withdrawal threshold (pMWT) and paw thermal withdrawal latency (pTWL) of each group were detected at different time points after surgery. The expression of myelin markers, autophagy markers and NLRP3 in ammasome-related molecul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Wu et al found that Clec7a knockdown can ameliorate NP in vivo and in vitro by targeting NLRP3 inflammasome-stimulated pyroptosis (Wu et al, 2022). In chronic constriction injury-induced NP rat models, BoNT/A functions as an NLRP3 inflammasome inhibitor that decreases NLRP3 inflammasome component expression and IL-18 level, thus exhibiting analgesic effect (He et al, 2023). In line with previous findings, we observed a reduction in NLRP3, Caspase-1, and GSDMD protein expression along with a decline of IL-1β and IL-18 production in vivo and in vitro, suggesting the inhibition of NLRP3 inflammasome-mediated pyroptosis in PHN.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al found that Clec7a knockdown can ameliorate NP in vivo and in vitro by targeting NLRP3 inflammasome-stimulated pyroptosis (Wu et al, 2022). In chronic constriction injury-induced NP rat models, BoNT/A functions as an NLRP3 inflammasome inhibitor that decreases NLRP3 inflammasome component expression and IL-18 level, thus exhibiting analgesic effect (He et al, 2023). In line with previous findings, we observed a reduction in NLRP3, Caspase-1, and GSDMD protein expression along with a decline of IL-1β and IL-18 production in vivo and in vitro, suggesting the inhibition of NLRP3 inflammasome-mediated pyroptosis in PHN.…”
Section: Discussionmentioning
confidence: 99%